Women Proficiency for Global Crises Management in Ethiopia (International Journal of Scientific Research and Management (IJSRM), 2020)
The COVID-19 virus is a new pathogen that is highly contagious, can spread quickly, and considered capable of causing enormous health, economic and societal impacts in any setting. According to WHO report, about (78%-85%) human-to-human transmission of the COVID-19 virus is the household transmission have occurred in families. The main purpose of this article is to assess the potential of women in crises management. These findings suggest that, women leadership has a potential advantage in crises management mainly because, women are on average more likely than men to adopt a relational approach to leadership. So that Ethiopia, will benefit more , hence the country’s more than half of the population and 50% of top-level leaders are women as a golden opportunity for Ethiopia to easily overcome this pandemic crisis by engaging a full potential of women at all levels. I recommend for Ethiopian government to use this acknowledged golden opportunity of having more women leaders especially at top-level and having women more than half of the population by mobilizing this women force up to family level to overcome this pandemic disease more better than any countries in the world.